INTESTINAL PARASITIC FAUNA AND PREVALENCE IN AFRICAN GIANT RAT (Cricetomys gambianus) IN NSUKKA METROPOLIS SOUTH EASTERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
to combat food insecurity and malnutrition among the local populace. However, the giant rat has been reported to harbour many parasites thus, its close association with man in raising them as mini-livestock and the consumption of the meat could be a public health risk to individuals handling them. This study was conducted to investigate the gut parasites and their prevalence on African giant rat in Nsukka metropolis. A total of 21 giant rats comprising 13 males and 8 females were trapped for the study. The giant rats were dissected, and the guts were removed and searched for parasites. A total of 506 parasites where recovered. Four different parasites Trichostrongylus sp., Trichuris muris (nematodes) and Hymenolepis diminuta and Taenia sp. (Platyhelminthes) were identified in the gastrointestinal tract of the giant rats. Hymenolepis diminuta was the most prevalent (100%) while Taenia sp. had the highest mean intensity of 10.15 (7.46 – 12.85, 95% CI) followed by Trichostrongylus sp. Taenia sp. is significantly higher in the caecum of males than the females (p< 0.05). The weight of African giant rat has positive correlation with the prevalence and intensity of the parasites. Given the parasitic load of African giant rats it is recommended that the giant rat should be reared to reduce the intensity of parasitic infection and increase the market value since the farmed ones will be regularly dewormed.
Keywords: Giant rat, nematode, Nsukka, parasite, platyhelminthes